Analisis Upaya Strategis dalam Memaksimalkan Penerapan Pelayanan Publik Berbasis E-Government di Desa - Zakly Hanafi Ahmad; Mukhammad Akhmad Najich Alfayn; Akhdiva Elfi Istiqoh (Universitas Batanghari Jambi, 2022)
E-Government is a new innovation in the implementation of public services in village government. The high number of internet users in Indonesia is the initial capital for implementing E-Government in maximizing public services in villages. The implementation of E-Government is also one of the steps to support good governance in Indonesia. The purpose of this study is to analyze how strategic steps can be taken to maximize E-Government-based public services in the village. The method used in this study is a qualitative research method using a literature review approach, in collecting data the authors collect data and information related to the implementation of E-Government in the village. Supporting data comes from research journal articles, supporting books, and online news. The results showed that in maximizing the implementation of E-Government-based public services, strategic steps must be taken, namely firstly improving the quality of the village apparatus, secondly conducting socialization to the community about the application of E-Government and thirdly conducting evaluations as a form of supervision in the implementation of village E-Government.